Kształtowanie języka mówionego ucznia a nauczanie literatury (założenia metodologiczne) = Shaping of the Pupil's Spoken Language and Teaching Literature (methodical presuppositions) - Kania, Stanisław (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This article presents a problem, which has been only little examined so far and which has been omitted in Polish didactics of the native language. The author gives attention to the bet, that the mere concept of "spoken language" has not yet been precisely defined in linguistic literature.
Keywords: dydaktyka literatury; język mówiony; nauczanie